The influence of environmental performance and good corporate governance on firm value with financial performance as a mediating variable - Sindu, Karlina Mechtildis; Rahyuda, Henny (International Journal Labs, 2025)
This study aims to analyze the effect of environmental performance and good corporate governance on firm value with financial performance as a mediating variable in basic material sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. This type of research is quantitative using purposive sampling method so that a sample of 19 companies is obtained. The data analysis technique used is the dynamic panel data regression method with the system generalized method of moments (GMMsystem ) approach using the RStudio application and the sobel test. This research found that environmental performance and GCG as measured by the independent board of commissioners have a significant positive effect on financial performance. Environmental performance, GCG as measured by the audit committee and financial performance have a significant positive effect on firm value. Financial performance is able to mediate the effect of environmental performance and GCG as measured by the independent board of commissioners on firm value. GCG as measured by the audit committee has a significant negative effect on financial performance, GCG as measured by the independent board of commissioners has a significant negative effect on firm value and financial performance is able to mediate the effect of the audit committee on firm value in a negative direction. Company management is advised to improve environmental performance management, GCG as measured by the independent board of commissioners, audit committee, and financial performance in order to increase company value.